2012
DOI: 10.1146/annurev-psych-120710-100452
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Method Bias in Social Science Research and Recommendations on How to Control It

Abstract: Despite the concern that has been expressed about potential method biases, and the pervasiveness of research settings with the potential to produce them, there is disagreement about whether they really are a problem for researchers in the behavioral sciences. Therefore, the purpose of this review is to explore the current state of knowledge about method biases. First, we explore the meaning of the terms "method" and "method bias" and then we examine whether method biases influence all measures equally. Next, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

105
8,983
18
106

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 10,956 publications
(9,212 citation statements)
references
References 110 publications
105
8,983
18
106
Order By: Relevance
“…Lance and Vandenberg, 2009;Lance et al, 2010). Although it could be argued that any inflated correlations due to common method variance are counterbalanced by the attenuating effect of measurement error as demonstrated by Lance and colleagues (2010), it is advisable that future studies testing the observed relationships in the present study also employ a hetero-method approach and procedural methods of control, believed to reduce common method variance (see Podsakoff et al, 2012). For example, archival data on accidents could be used as a proxy for risk behavior instead of self-reported measures.…”
Section: Limitations and Future Researchmentioning
confidence: 79%
“…Lance and Vandenberg, 2009;Lance et al, 2010). Although it could be argued that any inflated correlations due to common method variance are counterbalanced by the attenuating effect of measurement error as demonstrated by Lance and colleagues (2010), it is advisable that future studies testing the observed relationships in the present study also employ a hetero-method approach and procedural methods of control, believed to reduce common method variance (see Podsakoff et al, 2012). For example, archival data on accidents could be used as a proxy for risk behavior instead of self-reported measures.…”
Section: Limitations and Future Researchmentioning
confidence: 79%
“…Thus, there is a potential source for common method bias in our data (Podsakoff et al 2003). To control for this bias and to improve internal validity, we reversed some items in the questionnaire and separated several variables and items to eliminate proximity effects (Podsakoff et al 2012). In addition, we conducted a Harman's one-factor test (Podsakoff and Organ 1986).…”
Section: Resultsmentioning
confidence: 99%
“…To control for such bias, we deployed five specific procedural remedies ex ante as suggested by Podsakoff, MacKenzie and Podsakoff (2012) to maximize respondent motivation and ability to respond accurately. First, we deployed a proximal separation between the constructs for exploration and exploitation, by means of dedicated buffer items, to diminish the use of prior responses to answer subsequent questions (Podsakoff, MacKenzie, Lee, & Podsakoff, 2003).…”
Section: Limitationsmentioning
confidence: 99%